Water, civilisation and power: Sudan's hydropolitical economy and the Al-Ingaz revolution - Verhoeven, H (2012)
This thesis argues that state-building in Sudan in the modern era cannot be understood without a multilevel analysis of the links between water, civilisation and power. More particularly, it focuses on the hydropolitical economy of the Al-Ingaz Revolution since its launch in 1989. I analyse the efforts by Sudan's military-Islamist leaders at material and immaterial transformation of society through visions of hydro-engineering civilisation. “Economic Salvation” -the rescue of Sudan’s economy through a “hydro-agricultural mission” that will create an ‘Islamic’ middle class- is central to this ideology. The hydro-agricultural mission is a revolutionary attempt at Islamist state-building through a hyper-ambitious Dam Programme and an Agricultural Revival in Sudan’s riverain core. It intends to entrench Al-Ingaz in power by delivering for those riverain constituencies and external partners on the Arabian Peninsula and in East Asia deemed critical to continued hegemony. This thesis is fundamentally about Islamist Sudan's hydropolitical economy, but makes broader contributions. First, it highlights how, far from being exceptional, the hydro-agricultural mission is deeply embedded in historical ways of thinking about water, civilisation and power in Sudan and the Nile Basin more broadly, echoing assumptions, policy prescriptions and logics of political control and high-modernist development that have been salient for almost 200 years. In the past, grand state-building projects, predicated on the dream of controlling the water to control the people, have been characterised by high levels of violence and developmental mirages in the desert. I show why, under military-Islamist rule, this experience is being repeated in Sudan. Second, this thesis is situated in wider debates in the early 21st century, with fears about resources crunches proliferating amidst rising global commodity prices and the impact of climate change. The idea that environmental scarcity, as an exogenous variable, is the main shaper of societies and their politics is enduring, but both theoretically and empirically misguided. Moreover, it has often been manipulated by elites in processes of power and wealth accumulation that reproduce the very societal and ecological problems they claim to be resolving. I argue that the links between water, civilisation and power in Sudan highlight not just the endogeneity of environmental scarcity to political-economic processes, but also the violent consequences of a modernist paradigm that is seen by ruling elites as both enlightened science and the route to hegemony while reproducing conflict at the local, national and regional level.